Comb-shaped sulfonated lignin waterborne polyurethane as well as preparation method and application thereof

By introducing modified zwitterionic monomers and sulfonated lignin into bio-based aqueous polyurethanes, a polyurethane film with a comb-like structure is solved, and the mechanical properties and lack of self-healing function of bio-based aqueous polyurethanes in the prior art are poor after application. The problem of achieving high mechanical properties and self-repairing polyurethane films are suitable for fabrics and leathers.

CN119390926AActive Publication Date: 2025-02-07SHENZHEN XIANGGAN SCIENCE & TECHNOLOGY ACHIEVEMENTS TRANSFORMATION CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411242059.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-02-07
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

When applied to fabrics or leather, existing bio-based water-based polyurethanes are susceptible to ultraviolet rays, their mechanical properties are not ideal, and their self-healing functions are lacking, resulting in a short service life.

Method used

Using comb-like sulfonated lignin aqueous polyurethane, a polyurethane film with ultra-tension properties and self-healing functions is formed by introducing modified zwitterionic monomers and sulfonated lignin.

Benefits of technology

It significantly improves the mechanical properties and self-healing properties of bio-based water-based polyurethane, imparts ultraviolet and antibacterial properties to fabrics or leather, extends service life, and has a green and environmentally friendly process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390926A_ABST
    Figure CN119390926A_ABST
Patent Text Reader

Abstract

The invention discloses comb-shaped sulfonated lignin waterborne polyurethane as well as a preparation method and application thereof. The resin is mainly prepared from the following raw materials in parts by weight through condensation polymerization: 3 to 50 parts of diisocyanate, 5 to 45 parts of polydihydric alcohol, 2 to 35 parts of modified zwitterionic monomer, 2 to 10 parts of hydroxyethyl disulfide, 5 to 20 parts of sulfonated modified lignin, 0.1 to 2 parts of catalyst and 50 to 150 parts of deionized water. The polyurethane resin coating film prepared by the method is excellent in mechanical property, superelasticity and light in surface color; when the resin is used for fabric coating or printing, the fabric can be endowed with self-repairing, anti-ultraviolet and antibacterial properties and the like, the preparation process is green and environment-friendly, and the prepared polyurethane can be applied to the fields of fabric, leather, automotive trim, wood and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane preparation, and in particular to a comb-shaped sulfonated lignin waterborne polyurethane and a preparation method and application thereof. Background Art

[0002] Ordinary polyester waterborne polyurethane has problems such as poor water resistance and poor mechanical properties. Waterborne polyurethane uses grafting or block chain extenders and blends to form a cross-linked network, which can improve its shortcomings and broaden its application areas. The introduction of phosphorylcholine groups enhances the degree of microphase separation and forms denser hydrogen bonds in hard segments of uniform size. The film exhibits good tensile properties and slow hydrolysis degradation rate, and has good low-temperature flexibility, low surface tension, weather resistance and other advantages. Combining with polyurethane can effectively improve flexibility and biocompatibility. In addition, the research on biomass materials from animal and plant resources is very active. Biomass has the advantages of being renewable, widely available and low-priced. If biomass monomers are introduced into polyurethane materials, it can not only improve the mechanical properties, water resistance and degradability of polyurethane, but also have the advantages of being green and degradable of natural materials. People are eager to find a method that can protect resins from ultraviolet radiation for a long time and improve their stability. Therefore, the introduction of some special functional monomers into polyurethane can also improve the durability of polyurethane in textiles and expand its application areas.

[0003] In the preparation of existing bio-based waterborne polyurethanes, bio-based monomers are often directly introduced into polyurethanes. The bio-based waterborne polyurethanes obtained in this way can have the following functions: good thermal stability, good room temperature biodegradability, and can also increase the solid content of waterborne polyurethanes. However, after the bio-based waterborne polyurethanes in the prior art are applied to substrates such as fabrics or leather, they will be affected by ultraviolet rays, and the mechanical properties are not ideal. Patent CN202310540644.9 discloses a method for preparing a lignin-based polyurethane elastomer, which is prepared from polyether polyols, modified lignin, catalysts and isocyanates. The tensile strength and elongation at break of the elastomer are increased, but the mechanical properties are still not ideal, and the resin is solvent-based. Patent CN202211369453.2 reports a lignin-based waterborne polyurethane emulsion, which is composed of lignin, oligomer polyols, polyisocyanates, hydrophilic chain extenders, polyol compounds, organic solvents, etc. Compared with the prior art, the lignin-based waterborne polyurethane emulsion has functional characteristics such as stability, low cost, green environmental protection, high mechanics, UV resistance, antibacterial, and hydrophobicity, and also realizes the high-value utilization of lignin as a renewable resource. Although the mechanical properties of the emulsion coating prepared by the above method have been improved, the mechanical properties of the coating are not good enough, and because it does not have a self-repairing function, the service life of the coating will be affected after experiencing the lasting effect of external force. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a comb-shaped sulfonated lignin waterborne polyurethane. The comb-shaped sulfonated lignin waterborne polyurethane with a specific composition of the present invention improves the mechanical properties and self-repairing properties of bio-based waterborne polyurethane. When applied to the surface of fabrics, the fabrics can be endowed with anti-ultraviolet and antibacterial properties, thereby solving the problems of dark color and durability of lignin-based fabric coatings. The comb-shaped sulfonated lignin waterborne polyurethane prepared by the present invention not only has stronger mechanical stress, but is also a waterborne polyurethane, green and environmentally friendly, and has an outstanding self-repairing function.

[0005] The invention also provides a preparation method and application of the comb-shaped sulfonated lignin waterborne polyurethane.

[0006] Technical solution: In order to achieve the above-mentioned purpose, the comb-shaped sulfonated lignin water-based polyurethane described in the present invention comprises the following raw materials in parts by weight: 3-50 parts of diisocyanate, 5-45 parts of polyglycol, 2-35 parts of modified zwitterionic monomer, 2-10 parts of 2-hydroxyethyl disulfide, 5-20 parts of sulfonated lignin, 0.1-2 parts of catalyst and 50-150 parts of deionized water.

[0007] Wherein, the diisocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.

[0008] Wherein, the polyglycol is one or more of polyethylene glycol, polypropylene glycol, polycaprolactone glycol and polytetrahydrofuran diol.

[0009] Preferably, the molecular weight of the polyglycol is 600-4000.

[0010] Wherein, the catalyst is one or more of N,N-dimethylcyclohexylamine, N,N'-dimethylpyridine, stannous octoate and dibutyltin dilaurate.

[0011] Wherein, the preparation steps of the modified zwitterionic monomer are as follows:

[0012] 0.5-10 parts of mercaptodiol monomer, 0.5-10 parts of zwitterionic monomer, 0.1-0.5 parts of azobisisovaleronitrile and 5-20 parts of acetone are uniformly mixed, and reacted at 40-80° C. for 1-6 hours to obtain a modified zwitterionic monomer; the zwitterionic monomer is one or more of methacryloylethyl betaine, 1-vinyl-3-(propanesulfonic acid) imidazole inner salt, 2-methacryloyloxyethyl phosphorylcholine and 1-(2-methyl)acryloyl-3-(propanesulfonic acid) imidazole inner salt; the mercaptodiol monomer is one or more of 3-mercapto-1,2-propylene glycol and dithioerythritol.

[0013] Wherein, the preparation steps of the sulfonated lignin are as follows:

[0014] 2-20 parts of lignin monomers, 5-30 parts of sultone, 1-5 parts of sodium hydroxide and 20-50 parts of acetone are uniformly mixed, and reacted at 60-90° C. for 1-3 hours to obtain sulfonated modified lignin; the lignin monomer is one or more of alkaline lignin and dealkalized lignin; the sultone is one or more of 1,4-butanesultone and 1,3-propanesultone.

[0015] The method for preparing the comb-shaped sulfonated lignin waterborne polyurethane of the present invention comprises the following steps:

[0016] Diisocyanate, polydiol and catalyst are added to acetone and mixed evenly, then an inert gas is introduced, the system is heated, and then modified zwitterionic monomer and 2-hydroxyethyl disulfide are added to the system to continue heating reaction, and sulfonated lignin is further added to the system to heat reaction, and finally the system temperature is lowered, and then deionized water is added to the system and mixed evenly to obtain sulfonated modified biomass-based waterborne polyurethane.

[0017] The system is heated to 40-80°C for reaction for 1-3 hours, and then the modified zwitterionic monomer and hydroxyethyl disulfide are added to the system to continue the reaction for 1-3 hours, and the sulfonated lignin is further added to the system to react for 2-5 hours. Finally, the system temperature is lowered to below 40°C, and then deionized water is added to the system and mixed to obtain the sulfonated modified biomass-based waterborne polyurethane.

[0018] The comb-shaped sulfonated lignin waterborne polyurethane of the invention is used in the fields of fabrics, leather, automobile interior decoration and wood.

[0019] The comb-shaped sulfonated lignin waterborne polyurethane can be coated on the surface of the substrate by dipping, rolling, spraying and printing, and dried at 40-80° C. to form a film.

[0020] Furthermore, the thickness of the polyurethane film is 40-200 μm.

[0021] The modified zwitterionic monomer prepared in the present invention can be successfully grafted into polyurethane to increase the molecular weight of polyurethane, and the introduced zwitterionic monomers undergo nucleophilic substitution or covalent bonding (i.e., forming ionic bonds) with the hydroxyl groups on the textile or leather, thereby improving the adhesion of the coating on the surface of the textile or leather and imparting good water fastness. On the other hand, the tensile strength and self-repairing efficiency of the polyurethane coating can be improved based on the side chain zwitterionic characteristics.

[0022] Furthermore, in the method for preparing sulfonated lignin of the present invention, the phenolic hydroxyl group and sultone in the lignin molecule undergo a sulfonation reaction, so that the molecule is connected with a sulfite bond, which is further extended and introduced into the polyurethane, which not only improves the hydrophilicity of the polyurethane, but also when the water-based polyurethane is applied to textiles or leather, the end-capping of the lignin gives the fabric or leather excellent UV protection and antibacterial effects.

[0023] The present invention can not only improve the flexibility of polyurethane by introducing modified zwitterionic monomers, but also increase the biocompatibility and antibacterial properties of polyurethane. The introduction of phosphorylcholine groups enhances the degree of microphase separation and improves the hydrolytic degradation of the film, and forms denser hydrogen bonds in the hard segments of uniform size, and the film exhibits good tensile properties and slow hydrolytic degradation rate; at the same time, it also meets the characteristics of full hand feel and comfort. The access of hydroxyethyl disulfide makes the modified polyurethane have good self-repairing properties. By adding sulfonated lignin, lignin is a biomaterial, which is green and environmentally friendly, improves the hydrophilicity of polyurethane, and makes polyurethane have anti-ultraviolet and antibacterial functions. Therefore, by combining the various formulas and the order of adding the various formulas in the specific preparation method of the present invention, a bio-based waterborne polyurethane with high tensile strength and anti-ultraviolet properties can be prepared, and the flexibility and anti-ultraviolet functions meet the requirements of subsequent application in textiles and leather. Here, it should be emphasized that the preparation order of the method of the present invention cannot be changed. Since sulfonated lignin has multiple hydroxyl groups, it should be added after the modified zwitterion is connected to the polyurethane prepolymer, so as to block the isocyanate group in the polyurethane chain. If the above preparation order is changed, the disulfide and zwitterion cannot be fully connected, which affects the self-repair and antibacterial properties. The sulfonated lignin in the present invention solves the problem that the original lignin brings too dark color to the film while retaining the anti-ultraviolet and antibacterial properties; the introduction of disulfide gives self-repair properties and increases the durability of the coating.

[0024] In the present invention, a zwitterionic monomer is first modified with mercaptodiol, and lignin is modified with sultone, and then the modified zwitterionic monomer, disulfide, and sulfonated lignin are sequentially introduced into a polyurethane prepolymer to obtain a biomass-based waterborne polyurethane. The polyurethane coating prepared by the present invention has excellent mechanical properties, superelasticity, and a lighter surface color; when the resin is used for fabric coating or printing, it can give the fabric self-repairing, UV resistance, and antibacterial properties. The preparation process of the present invention is green and environmentally friendly, and the prepared polyurethane can be used in the fields of fabrics, leather, automotive interiors, wood, etc.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0026] (1) The biomass-based waterborne polyurethane prepared by the present invention is based on zwitterionic monomers and lignin, and the polyurethane has a comb-like structure, has super tensile properties, excellent mechanical properties, super elasticity and a lighter surface color;

[0027] (2) The polyurethane is bio-based and degradable;

[0028] (3) The polyurethane can be applied to the surface of substrates such as fabrics and leather and impart excellent UV resistance and antibacterial properties;

[0029] (4) The polyurethane preparation process is simple and water is used as a solvent, which is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic flow chart of the preparation method of phosphorylcholine monomer grafted waterborne polyurethane in the present invention;

[0031] Figure 2 is an infrared spectrum characterization diagram of the waterborne polyurethane of the present invention;

[0032] Figure 3 is the nuclear magnetic hydrogen spectrum of the waterborne polyurethane of the present invention;

[0033] Figure 4 The healing effect of the waterborne polyurethane of the present invention;

[0034] Figure 5 The self-repairing process diagram of the polyurethane film under scratch and cut conditions in the present invention;

[0035] Figure 6 The ultraviolet absorption spectra of the coated fabrics at different lignin contents in the present invention;

[0036] Figure 7 is a graph of the UV protection index of coated fabrics at different lignin contents in the present invention;

[0037] Figure 8 This is a bacterial culture diagram on the surface of the polyurethane-coated fabric in the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described below with reference to the embodiments.

[0039] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0040] Example 1

[0041] According to parts by weight, sulfonated modified biomass-based waterborne polyurethane is prepared, such as Figure 1 As shown:

[0042] (1) 10 parts of 2-methacryloyloxyethyl phosphorylcholine, 10 parts of 3-mercapto-1,2-propanediol, 0.5 parts of azobisisovaleronitrile and 20 parts of acetone were mixed evenly and reacted at 80° C. for 6 hours to obtain modified phosphorylcholine.

[0043] (2) 5 parts of alkaline lignin (alkaline lignin, cas: 8068-05-1, Macklin L832292), 20 parts of 1,4-butane sultone, 5 parts of sodium hydroxide and 50 parts of acetone were mixed evenly, and reacted at 90° C. for 3 hours to obtain sulfonated lignin.

[0044] (3) First, 20 parts of polytetrahydrofuran ether diol (molecular weight 400), 45 parts of hexamethylene diisocyanate, 2 parts of dibutyltin dilaurate and 100 parts of acetone were mixed evenly, purged with high-purity nitrogen for 30 minutes, and then reacted at 80°C for 3 hours to obtain a prepolymer; 10 parts of modified phosphorylcholine monomer and 8 parts of 2-hydroxyethyl disulfide were added to the above prepolymer, and the reaction was continued at 80°C for 3 hours, and 5 parts of sulfonated lignin were added to the prepolymer and the reaction was continued at 80°C for 5 hours. Finally, the system temperature was reduced to below 40°C, and then 150 parts of deionized water were added to the system and mixed evenly to obtain a sulfonated modified biomass-based waterborne polyurethane.

[0045] (4) The bio-based waterborne polyurethane was coated on the surface of the cotton fabric by brushing, and then dried at 80° C. to obtain a polyurethane coated fabric with a coating thickness of 200 μm.

[0046] The infrared spectrum characterization diagram and nuclear magnetic hydrogen spectrum diagram of the waterborne polyurethane prepared in this embodiment are as follows: Figure 2 and Figure 3 The infrared peak of excess -NCO observed in the prepolymer is located at 2260 cm -1 , while the polymers showed no obvious absorption peaks, indicating that -NCO was consumed by -OH monomers and formed elastomers. -1 and 2862cm -1 The absorption peak at 3310 cm is attributed to the vibration of methyl and methylene groups. -1 and 1729cm -1 The absorption peak at 1380 cm corresponds to the stretching vibration of the -NH bond and the stretching vibration of the carbonyl group in isocyanate. -1 The infrared peak at 1246 cm -1 The peaks at 3.79 ppm and 1.64 ppm correspond to the C=O vibration of lignin. These two peaks provide strong evidence for the introduction of waterborne polyurethane end groups into lignin. The proton signals at 3.79 ppm and 1.64 ppm correspond to the -CH near the ether bond and carbonyl group in the soft segment. 2 unit, while the signal at 3.30 ppm corresponds to the terminal CH2 The proton signals at 2.93 ppm and 1.39 ppm are mainly related to the alkyl groups in the hard segment units. The proton signal at 4.0 ppm confirms the formation of the polyurethane bond. The proton signals in the range of 0.89 to 1.39 ppm correspond to -CH 3 , -CH and N+–CH 3 In addition, proton signals of terminal sulfonated lignin were observed at 8.0 ppm, 2.78 ppm, and 0.93 ppm. The chemical structure of the polyurethane was confirmed by 1H NMR and FT-IR, indicating that the polyurethane was successfully synthesized.

[0047] The preparation of zwitterionic monomers and sulfonated lignin in the following controls is the same as in Example 1:

[0048] Preparation method of control polyurethane 1 (compared with Example 1, only zwitterionic monomer and sulfonated lignin are not included): First, 20 parts of polytetrahydrofuran ether glycol (molecular weight 400), 45 parts of hexamethylene diisocyanate, 2 parts of dibutyltin dilaurate and 100 parts of acetone are mixed evenly, then purged with high-purity nitrogen for 30 minutes, and then reacted at 80°C for 3 hours to obtain a prepolymer; 8 parts of 2-hydroxyethyl disulfide are added to the above prepolymer, and the reaction is continued at 80°C for 8 hours, and finally the system temperature is reduced to below 40°C, and then 150 parts of deionized water are added to the system and mixed evenly to obtain a biomass-based waterborne polyurethane. The above waterborne polyurethane is applied to the surface of cotton fabric by brushing, and dried at 80°C to obtain a polyurethane coated fabric with a coating thickness of 200 μm.

[0049] Preparation method of control polyurethane 2 (compared with Example 1, only zwitterionic monomer is not included): first, 20 parts of polytetrahydrofuran ether glycol (molecular weight 400), 45 parts of hexamethylene diisocyanate, 2 parts of dibutyltin dilaurate and 100 parts of acetone are mixed evenly, then purged with high-purity nitrogen for 30 minutes, and then reacted at 80°C for 3 hours to obtain a prepolymer; 8 parts of 2-hydroxyethyl disulfide are added to the above prepolymer, and the reaction is continued at 80°C for 3 hours, and 5 parts of sulfonated lignin are added to the prepolymer and the reaction is continued at 80°C for 5 hours, and finally the system temperature is lowered to below 40°C, and then 150 parts of deionized water are added to the system and mixed evenly to obtain a biomass-based waterborne polyurethane. The above waterborne polyurethane is applied to the surface of cotton fabric by brushing, and dried at 80°C to obtain a polyurethane coated fabric with a coating thickness of 200 μm.

[0050] Preparation method of control polyurethane 3 (compared with Example 1, only sulfonated lignin is not included): first, 20 parts of polytetrahydrofuran ether glycol (molecular weight 400), 45 parts of hexamethylene diisocyanate, 2 parts of dibutyltin dilaurate and 100 parts of acetone are mixed evenly, then purged with high-purity nitrogen for 30 minutes, and then reacted at 80°C for 3 hours to obtain a prepolymer; 10 parts of modified phosphorylcholine monomer and 8 parts of 2-hydroxyethyl disulfide are added to the above prepolymer, and the reaction is continued at 80°C for 8 hours, and finally the system temperature is reduced to below 40°C, and then 150 parts of deionized water are added to the system and mixed evenly to obtain a biomass-based waterborne polyurethane. The above waterborne polyurethane is applied to the surface of cotton fabric by brushing, and dried at 80°C to obtain a polyurethane coated fabric with a coating thickness of 200 μm.

[0051] Preparation method of control polyurethane 4 (compared with Example 1, only sulfonated lignin is added first and then modified zwitterions are added): first, 20 parts of polytetrahydrofuran ether diol (molecular weight 400), 45 parts of hexamethylene diisocyanate, 2 parts of dibutyltin dilaurate and 100 parts of acetone are mixed evenly, then purged with high-purity nitrogen for 30 minutes, and then reacted at 80°C for 3 hours to obtain a prepolymer; 5 parts of modified sulfonated lignin monomer and 8 parts of 2-hydroxyethyl disulfide are added to the above prepolymer, and after continuing to react at 80°C for 3 hours, 8 parts of modified phosphorylcholine monomer are added and reacted at 80°C for 5 hours, and finally the system temperature is lowered to below 40°C, and then 150 parts of deionized water are added to the system and mixed evenly to obtain a biomass-based waterborne polyurethane. The above waterborne polyurethane is applied to the surface of cotton fabric by brushing, and dried at 80°C to obtain a polyurethane coated fabric with a coating thickness of 200 μm.

[0052] Example 2

[0053] (1) 1.2 parts of methacryloylethyl betaine, 3 parts of dithioerythritol, 0.3 parts of azobisisovaleronitrile and 12 parts of acetone were mixed evenly and reacted at 65° C. for 3 hours to obtain modified betaine.

[0054] (2) 12 parts of dealkalized lignin (lignin (dealkalized), cas: 9005-53-2, Aladdin L195713), 22 parts of 1,3-propane sultone, 3 parts of sodium hydroxide and 25 parts of acetone were mixed evenly, and reacted at 75° C. for 2 hours to obtain sulfonated lignin.

[0055] (3) First, 25 parts of polycaprolactone diol (molecular weight 2000), 13 parts of isophorone diisocyanate, 1.1 parts of stannous octoate and 60 parts of acetone were mixed uniformly, purged with high-purity nitrogen for 30 minutes, and then reacted at 65°C for 2 hours to obtain a prepolymer; 5.5 parts of modified betaine monomer and 4.5 parts of hydroxyethyl disulfide were added to the above prepolymer, and the reaction was continued at 65°C for 2 hours, and 4 parts of sulfonated lignin were added to the prepolymer and the reaction was continued at 65°C for 3 hours. Finally, the system temperature was reduced to below 40°C, and then 110 parts of deionized water were added to the system and mixed uniformly to obtain a sulfonated modified biomass-based waterborne polyurethane.

[0056] (4) The bio-based waterborne polyurethane was coated on the surface of the cotton fabric by spraying, and then dried at 60° C. to obtain a polyurethane coated fabric with a coating thickness of 100 μm.

[0057] Example 3

[0058] (1) 0.5 parts of 1-vinyl-3-(propanesulfonic acid) imidazole inner salt, 0.5 parts of 3-mercapto-1,2-propanediol, 0.1 parts of azobisisovaleronitrile and 5 parts of acetone were mixed evenly and reacted at 40° C. for 1 hour to obtain a modified imidazole salt.

[0059] (2) 2 parts of alkaline lignin, 5 parts of 1,4-butane sultone, 1 part of sodium hydroxide and 20 parts of acetone were uniformly mixed and reacted at 60° C. for 1 hour to obtain sulfonated lignin.

[0060] (3) First, 5 parts of polyethylene glycol (molecular weight 4000), 3 parts of diphenylmethane diisocyanate, 0.1 parts of N,N'-dimethylpyridine and 30 parts of acetone were mixed evenly, purged with high-purity nitrogen for 30 minutes, and then reacted at 40°C for 1 hour to obtain a prepolymer; 2 parts of modified imidazole salt monomer and 2 parts of hydroxyethyl disulfide were added to the above prepolymer, and the reaction was continued for 1 hour, and 5 parts of sulfonated lignin were added to the prepolymer and the reaction was continued for 2 hours. Finally, the system temperature was reduced to below 40°C, and then 50 parts of deionized water were added to the system to obtain a sulfonated modified biomass-based waterborne polyurethane.

[0061] (4) The bio-based waterborne polyurethane was coated on the surface of the cotton fabric by spraying, and then dried at 40° C. to obtain a polyurethane coated fabric with a coating thickness of 40 μm.

[0062] Example 4

[0063] (1) 0.8 parts of 1-(2-methyl)acryloyl-3-(propanesulfonic acid) imidazole inner salt, 1 part of dithioerythritol, 0.2 parts of azobisisovaleronitrile and 8 parts of acetone were mixed evenly and reacted at 50° C. for 2 hours to obtain a modified imidazole inner salt.

[0064] (2) 8 parts of dealkalized lignin, 10 parts of 1,3-propane sultone, 2 parts of sodium hydroxide and 30 parts of acetone were mixed evenly, and reacted at 70° C. for 2 hours to obtain sulfonated lignin.

[0065] (3) First, 5 parts of polypropylene glycol (molecular weight 800), 3 parts of toluene diisocyanate, 0.1 parts of N,N-dimethylcyclohexylamine and 30 parts of acetone are mixed evenly, and then purged with high-purity nitrogen for 30 minutes, and then reacted at 40°C for 1 hour to obtain a prepolymer; 3 parts of modified imidazole inner salt monomer and 3.5 parts of hydroxyethyl disulfide are added to the above prepolymer, and the reaction is continued for 2 hours, and then 8 parts of sulfonated lignin are added to the prepolymer and the reaction is continued for 3 hours. Finally, the system temperature is reduced to below 40°C, and then 70 parts of deionized water are added to the system to obtain a sulfonated modified biomass-based waterborne polyurethane.

[0066] (4) The bio-based waterborne polyurethane was coated on the surface of cotton fabric by printing, and dried at 50° C. to obtain polyurethane coated fabric with a coating thickness of 80 μm.

[0067] Example 5

[0068] (1) 1.5 parts of methacryloyloxyethyl phosphorylcholine, 4 parts of dithioerythritol, 0.4 parts of azobisisovaleronitrile and 15 parts of acetone were mixed evenly and reacted at 70° C. for 5 hours to obtain modified phosphorylcholine.

[0069] (2) 15 parts of alkaline lignin, 23 parts of 1,4-butane sultone, 3.5 parts of sodium hydroxide and 45 parts of acetone were uniformly mixed and reacted at 80° C. for 2 hours to obtain sulfonated lignin.

[0070] (3) First, 40 parts of polycaprolactone diol (molecular weight 1000), 16 parts of isophorone diisocyanate, 1.5 parts of dibutyltin dilaurate and 80 parts of acetone were mixed evenly, purged with high-purity nitrogen for 30 minutes, and then reacted at 70°C for 2 hours to obtain a prepolymer; 8 parts of modified phosphorylcholine monomer and 7 parts of hydroxyethyl disulfide were added to the above prepolymer, and the reaction was continued for 2 hours. Then, 15 parts of sulfonated lignin were added to the prepolymer and the reaction was continued for 4 hours. Finally, the system temperature was reduced to below 40°C, and then 120 parts of deionized water were added to the system to obtain a sulfonated modified biomass-based waterborne polyurethane.

[0071] (4) The bio-based waterborne polyurethane was coated on the surface of cotton fabric by printing, and dried at 70° C. to obtain polyurethane coated fabric with a coating thickness of 160 μm.

[0072] Example 6

[0073] The biomass-based waterborne polyurethane was subjected to a tensile test using a universal testing machine, and the mechanical properties of the polyurethane elastomer were tested and analyzed using a microcomputer-controlled electronic universal testing machine. Specifically, the waterborne polyurethane prepared in Examples 1-5 was poured into a dumbbell-shaped polytetrafluoroethylene mold, and placed in an oven at 80°C for 6 hours to obtain a polyurethane elastomer. The tensile rate of the testing machine was set to 200 mm / min. The mechanical properties of the polyurethane elastomers prepared in Examples 1-5 and the control samples 1-4 were measured, and the results are shown in Table 1.

[0074] Table 1 Mechanical properties of polyurethane elastomers

[0075] Tensile strength(MPa) Elongation at break (%) Example 1 56.8 834 Example 2 43.7 688 Example 3 41.9 597 Example 4 55.9 625 Example 5 54.8 601 Control sample 1 5.9 125 Control sample 2 30.5 476 Control sample 3 34.2 524 Control sample 4 40.5 574

[0076] As can be seen from Table 1, compared with the control polyurethane, the polyurethane film of the present invention has superior mechanical properties, and the tensile strength and elongation at break are far greater than the control polyurethane. This is mainly due to the interaction between the polyurethane comb structure and the zwitterions and the hydrogen bonding force provided by lignin, specifically the force between the positive and negative ion bonds, and the sparse structure can help maximize the force; at the same time, a large number of hydrogen bonds play a synergistic role. It can be seen from the above control sample that in the present invention, if the zwitterion monomer and sulfonated lignin are not added at the same time, the mechanical properties will be significantly reduced, indicating that the two have a synergistic effect in the system. In addition, the zwitterion monomer must be added first and then the sulfonated lignin during preparation. If the order of adding the two is changed, the sulfonated lignin with a polyhydroxy structure will react all isocyanate groups, and the zwitterion monomer will not be able to access, which will also affect the effect to a certain extent.

[0077] In addition, in the present invention, biomass material lignin and zwitterionic monomers are introduced into polyurethane; if DMBA is used instead of sulfonated lignin end-capping in Example 1, the mechanical properties of the elastomer are significantly reduced (tensile strength 12.1 MPa, elongation at break 280%); or if 2-hydroxyethyl disulfide is replaced in Example 1, the self-healing effect of the film is also significantly reduced. The polyurethane prepared in Example 1 is as follows Figure 4 a, showing a gradual and significant healing effect, reaching 29% and 63% repair rates after 1 hour and 2 hours, respectively, at room temperature. In contrast, under the same conditions, replacing 2-hydroxyethyl disulfide showed a smaller healing effect ( Figure 4 b).

[0078] Example 7

[0079] The polyurethane film prepared in Example 1 was tested, and the morphological changes of scratches during the self-repair process of the PU coating were recorded using an optical microscope. The magnifications of the objective lens and the eyepiece were ×10 and ×10, respectively. Figure 5As shown, the polyurethane synthesized in Example 4 has self-repairing ability. No matter it is scratched or cut, the coating film can be repaired within 4 minutes at 60°C. This is mainly due to the dynamic reversible assembly of ionic bonds and disulfide bonds between zwitterions.

[0080] Example 8

[0081] According to the preparation method of Example 1, the UPF value and UV protection index of the coated fabrics with different lignin contents were measured using a cotton fabric UV transmittance tester according to the AATCC 183-2020 standard. Figure 6 and Figure 7 It can be found that when the content of sulfonated lignin in the system reaches 6% or more, the ultraviolet protection index (UPF) of the fabric coating can reach more than 50, or even exceed 100, indicating that the polyurethane coated fabric with this content has good anti-ultraviolet performance.

[0082] Example 9

[0083] The antibacterial performance of the polyurethane film prepared in Example 1 was tested, and the antibacterial effect of the water-based polyurethane film on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was evaluated by the shake bottle method. Three parallel control samples were set for all samples, and the antibacterial performance of all samples was tested according to GB / T 20944.3-2008. Figure 8 As shown, the polyurethane coated fabric in Example 3 has excellent antibacterial properties, while the control sample has a lot of Staphylococcus aureus and Escherichia coli on the surface, which is mainly due to the presence of zwitterions and lignin in the coating.

[0084] Example 10

[0085] Two kinds of branches, multiple branched structures in the polyurethane macromolecular chain, the charge attraction between positive and negative ions makes them distributed in a comb-like and orderly manner. Through the K / S value test, the film capped with sulfonated lignin after modification is lighter in color and has good application prospects on fabrics. By comparing Examples 1-4, the polyurethane with the best performance is tested and compared as Example 1.

[0086]

Claims

1. A comb-shaped sulfonated lignin waterborne polyurethane, characterized in that: The invention comprises the following raw materials in parts by weight: 3-50 parts of diisocyanate, 5-45 parts of polyglycol, 2-35 parts of modified zwitterionic monomer, 2-10 parts of 2-hydroxyethyl disulfide, 5-20 parts of sulfonated lignin, 0.1-2 parts of catalyst and 50-150 parts of deionized water.

2. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The diisocyanate is one or more of hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate and diphenylmethane diisocyanate.

3. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The polyglycol is one or more of polyethylene glycol, polypropylene glycol, polycaprolactone glycol and polytetrahydrofuran diol.

4. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The catalyst is one or more of N,N-dimethylcyclohexylamine, N,N'-dimethylpyridine, stannous octoate and dibutyltin dilaurate.

5. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The preparation steps of the modified zwitterionic monomer are as follows: 0.5-10 parts of mercaptodiol monomer, 0.5-10 parts of zwitterionic monomer, 0.1-0.5 parts of azobisisovaleronitrile and 5-20 parts of acetone are uniformly mixed, and reacted at 40-80° C. for 1-6 hours to obtain a modified zwitterionic monomer; the zwitterionic monomer is one or more of methacryloylethyl betaine, 1-vinyl-3-(propanesulfonic acid) imidazole inner salt, 2-methacryloyloxyethyl phosphorylcholine and 1-(2-methyl)acryloyl-3-(propanesulfonic acid) imidazole inner salt; the mercaptodiol monomer is one or more of 3-mercapto-1,2-propylene glycol and dithioerythritol.

6. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The preparation steps of the sulfonated lignin are as follows: 2-20 parts of lignin monomers, 5-30 parts of sultone, 1-5 parts of sodium hydroxide and 20-50 parts of acetone are uniformly mixed, and reacted at 60-90° C. for 1-3 hours to obtain sulfonated modified lignin; the lignin monomer is one or more of alkaline lignin and dealkalized lignin; the sultone is one or more of 1,4-butanesultone and 1,3-propanesultone.

7. A method for preparing the comb-shaped sulfonated lignin waterborne polyurethane according to claim 1, characterized in that: The steps include: Diisocyanate, polydiol and catalyst are added to acetone and mixed evenly, then an inert gas is introduced, the system is heated, and then modified zwitterionic monomer and 2-hydroxyethyl disulfide are added to the system to continue heating reaction, and sulfonated lignin is further added to the system to heat reaction, and finally the system temperature is lowered, and then deionized water is added to the system and mixed evenly to obtain sulfonated modified biomass-based waterborne polyurethane.

8. The preparation method according to claim 7, characterized in that: The system is heated to 40-80°C for reaction for 1-3 hours, and then the modified zwitterionic monomer and hydroxyethyl disulfide are added to the system to continue the reaction for 1-3 hours, and the sulfonated lignin is further added to the system to react for 2-5 hours. Finally, the system temperature is lowered to below 40°C, and then deionized water is added to the system and mixed to obtain the sulfonated modified biomass-based waterborne polyurethane.

9. The comb-shaped sulfonated lignin waterborne polyurethane according to claim 1 is preferably used in the fields of fabrics, leather, automobile interiors and wood.

10. The use according to claim 9, characterized in that: The comb-shaped sulfonated lignin waterborne polyurethane can be coated on the surface of the substrate by dipping, rolling, spraying and printing, and dried at 40-80° C. to form a film.

Citation Information

Patent Citations

  • Preparation method of lignin-based aqueous polyurethane emulsion

    CN116023618B

  • Lignin-based polyurethane elastomer, preparation method and application

    CN116655875A

  • Pectinate polyurethane inflaming-retarding and water-repelling finishing agent as well as preparation method and application thereof

    CN107740278A

  • Preparation method of high-elasticity biological polyurethane foam

    CN116199849A

  • Pectinate solid-solid phase change material and its preparing process

    CN1247217A